Towards a practical management of fatigue in systemic lupus erythematosus - Thierry Martin; Matthias Schneider; Pierre-Edouard Gavand; Philippe Mertz; Aurélien Schlencker (Lupus Science and Medicine)
Significant fatigue is reported by two-thirds of patients with SLE and severe fatigue by one-third. The assessment and treatment of fatigue remains a major challenge in SLE, especially in patients with no disease activity. Here, we suggest a practical algorithm for the management of fatigue in SLE. First, common but non–SLE-related causes of fatigue should be ruled out based on medical history, clinical and laboratory examinations. Then, presence of SLE-related disease activity or organ damage should be assessed. In patients with active disease, remission is the most appropriate therapeutic target while symptomatic support is needed in case of damage. Both anxiety and depression are major independent predictors of fatigue in SLE and require dedicated assessment and care with psychological counselling and pharmacological intervention if needed. This practical algorithm will help in improving the management of one the most common and complex patient complaints in SLE.